Ex vivo culture of adult CD34+ stem cells using functional highly porous polymer scaffolds to establish biomimicry of the bone marrow niche. (December 2019) - Severn, C.E.; Eissa, A.M.; Langford, C.R.; Parker, A.; Walker, M.; Dobbe, J.G.G.; Streekstra, G.J.; Cameron, N.R.; Toye, A.M.
Abstract: Haematopoiesis, the process of blood production, occurs from a tiny contingent of haematopoietic stem cells (HSC) in highly specialised three-dimensional niches located within the bone marrow. When haematopoiesis is replicated using in vitro two-dimensional culture, HSCs rapidly differentiate, limiting self-renewal. Emulsion-templated highly porous polyHIPE foam scaffolds were chosen to mimic the honeycomb architecture of human bone. The unmodified polyHIPE material supports haematopoietic stem and progenitor cell (HSPC) culture, with successful culture of erythroid progenitors and neutrophils within the scaffolds. Using erythroid culture methodology, the CD34 + population was maintained for 28 days with continual release of erythroid progenitors. These cells are shown to spontaneously repopulate the scaffolds, and the accumulated egress can be expanded and grown at large scale to reticulocytes. We next show that the polyHIPE scaffolds can be successfully functionalised using activated BM(PEG)2 (1, 8-bismaleimido-diethyleneglycol) and then a Jagged-1 peptide attached in an attempt to facilitate notch signalling. Although Jagged-1 peptide had no detectable effect, the BM(PEG)2 alone significantly increased cell egress when compared to controls, without depleting the scaffold population. This work highlights polyHIPE as a novel functionalisable material for mimicking the bone marrow, and also that PEG can influence HSPC behaviour within scaffolds. Graphical abstract: Utilising polyHIPE scaffolds for the culture and analysis of human peripheral blood haematopoietic stem and progenitor cell expansion and proliferation.Image 1